2020
DOI: 10.3390/nu12123736
|View full text |Cite
|
Sign up to set email alerts
|

Lipidemic Profile Changes over a Two-Year Intervention Period: Who Benefited Most from the Feel4Diabetes Program?

Abstract: Identification of participants’ characteristics who benefited most from large community-based intervention studies may guide future prevention initiatives in order to maximize their effectiveness. The current study aimed to examine the socio-demographic, anthropometric, and behavioral characteristics, as well as the health and eating perceptions of those who improved their lipidemic profile, in the Feel4Diabetes early screening and prevention program. In the present analyses, 1773 adults from families at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…La dieta forma parte de unos de los pilares fundamentales de los tratamientos de los pacientes diabéticos y su conocimiento adecuado lo lleva a un mejor control de su enfermedad. (5,38) En este empeño se requiere un acercamiento a las personas para dirigir el aprendizaje y el conocimiento acerca de este aspecto, así como tratar el problema integralmente, tomando en cuenta la forma de pensar, las ansiedades, las creencias de salud de esas personas y el entorno familiar y social en el cual se desarrolla su vida diaria. (1) Se muestra el nivel de conocimiento sobre la utilización de la insulina antes y después de la intervención.…”
Section: Resultados Y Discusiónunclassified
“…La dieta forma parte de unos de los pilares fundamentales de los tratamientos de los pacientes diabéticos y su conocimiento adecuado lo lleva a un mejor control de su enfermedad. (5,38) En este empeño se requiere un acercamiento a las personas para dirigir el aprendizaje y el conocimiento acerca de este aspecto, así como tratar el problema integralmente, tomando en cuenta la forma de pensar, las ansiedades, las creencias de salud de esas personas y el entorno familiar y social en el cual se desarrolla su vida diaria. (1) Se muestra el nivel de conocimiento sobre la utilización de la insulina antes y después de la intervención.…”
Section: Resultados Y Discusiónunclassified
“…Specifically, regarding glycemic indices (fasting plasma glucose, insulin and glycosylated hemoglobin levels), Moschonis et al revealed that those who benefited most were males, younger people, and those with higher education, living in southern and eastern Europe, perceiving their body weight to be higher than normal [ 17 ]. Regarding their lipidemic profile, additional results from the Feel4Diabetes-study (Karatzi et al) showed that women, people living in southeastern Europe, coming from two-parent families, with self-perceived higher financial security, higher educational level, less emotional eating and less sedentary behavior, had a higher probability of benefit from the two-year intervention [ 18 ]. Oumrait et al revealed in a cross-sectional study that there are several social constraints, especially in socio-economically disadvantage populations, that must be addressed by future intervention studies for lifestyle modification [ 19 ].…”
mentioning
confidence: 99%